Nitrogen-doped-carbon-coated SnO2 nanoparticles derived from a SnO2@MOF composite as a lithium ion battery anode material. Issue 32 (5th April 2017) - Li, Fengcai; Du, Jia; Yang, Hao; Shi, Wei; Cheng, Peng
Abstract : A facile method was developed to combine MOF-derived N-doped carbon with SnO2 nanoparticles, which can cushion the volume change. The optimized SOC-3 composite achieved a reversible specific capacity of 1032 mA h g −1 after 150 cycles at 100 mA g −1 . Abstract : N-Doped-carbon-coated 2–4 nm SnO2 nanoparticles were synthesized via a facile metal–organic framework (MOF) coating process followed by a calcination of the SnO2 @MOF composite. The as-prepared SnO2 nanoparticles are well dispersed and coated with a uniform nitrogenous carbon structure, which can effectively prevent volume expansion during discharge and charge processes. Benefiting from the advantages of a synergistic effect of SnO2 nanoparticles and carbon structure, these materials exhibit excellent electrochemical performance. For the optimized material SOC-3, a reversible specific capacity of 1032 mA h g −1 was maintained at 100 mA g −1 after 150 cycles with a coulombic efficiency of 99%. When the current was increased to 500 mA g −1, a capacity of 600 mA h g −1 was still attained.